2012
DOI: 10.1042/cbi20110506
|View full text |Cite
|
Sign up to set email alerts
|

Neural crest stem cell property of apical pulp cells derived from human developing tooth

Abstract: Recent reports have described that NCSCs (neural crest-derived stem cells) are not only present in the embryonic neural crest but also in the adult tissues. Dental pulp is one of mesenchymal soft tissues origin from cranial neural crest cells, and thought to be a source of adult stem cells. Here, we investigated the existence of NCSC-like cells in apical pulp of human developing tooth. Human impacted third molars with immature apex freshly extracted were obtained. The cells derived from the apical pulp tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(114 citation statements)
references
References 31 publications
5
103
0
1
Order By: Relevance
“…has been also reported and linked to their embryonic origin [51, 52]. Sakai et al [53] have also shown that the majority of DPSCs and SHED expressed several neural lineage markers, including nestin, Doublecortin (DCX; neuronal progenitor cells), β III-tubulin (early neuronal cells), NeuN (mature neurons), GFAP (neural stem cells and astrocytes), S-100 (Schwann cells), A2B5, and CNPase (oligodendrocyte progenitor cells).…”
Section: Localization and Immunophenotypic Characterization Of Denmentioning
confidence: 99%
“…has been also reported and linked to their embryonic origin [51, 52]. Sakai et al [53] have also shown that the majority of DPSCs and SHED expressed several neural lineage markers, including nestin, Doublecortin (DCX; neuronal progenitor cells), β III-tubulin (early neuronal cells), NeuN (mature neurons), GFAP (neural stem cells and astrocytes), S-100 (Schwann cells), A2B5, and CNPase (oligodendrocyte progenitor cells).…”
Section: Localization and Immunophenotypic Characterization Of Denmentioning
confidence: 99%
“…This means that the source of cells can influence the transplantation results, which reflect the origin of the adult stem cells sources9,10,11. Notably, dental stem cells can differentiate into neural crest-derived cells, such as neurons and glial cells, because they are obtained from tissue within the neural crest13,14,15. In some reports, dental stem cells show better neural stem cell properties than bone marrow-derived mesenchymal stem cells 16.…”
Section: Introductionmentioning
confidence: 99%
“…6B). The Snail family members, Snail 1 and Slug, which encode zinc finger-type transcription factors, have been shown to be involved in neural crest formation and subsequent epithelial status (23,24). Consistent with microarray data, Slug expression was significantly increased in Nfic Ϫ/Ϫ pulp cells compared with wild type, whereas E-cadherin expression was decreased (Fig.…”
Section: Nfic Maintains Epithelial Differentiation Status In Odontoblmentioning
confidence: 99%